Baptism: A Guide to Life from Death - Leithart, Peter J. (Christian Essentials, 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Series Preface -- Chapter I: Family, Body, Temple -- Chapter II: Rites Old and New -- Chapter III: World from Water -- Chapter IV: Killing and Saving Flood -- Chapter V: A Cut in the Flesh -- Chapter VI: Drowning Pharaoh -- Chapter VII: An Ample Washing -- Chapter VIII: Crossing Jordan -- Chapter IX: Rain on Mown Grass -- Chapter X: Spirit of Prophecy -- Epilogue: To the Baptized -- Acknowledgments -- Translations Used -- Works Cited -- Author Index -- Scripture Index.